2022
DOI: 10.3390/en15051921
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Emission Reduction Effect and Spatial Difference of Carbon Emission Trading Policy in China

Abstract: To cope with huge carbon emission pressure, China has implemented a carbon emissions trading pilot policy that aims to provide reasonable suggestions for the smooth operation of the national carbon market. This paper selects the provincial panel data in China from 2005 to 2019 and uses the propensity score matching-difference in difference (PSM-DID) method to evaluate the carbon emission policy’s reduction effect. Based on carbon emissions (CE) and carbon emission intensity (CI), provinces and cities are divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…There are many literatures on the evaluation of the CETS's economic effect, mainly focusing on energy saving and emission reduction (Xuan et al, 2020;Tian et al, 2022), industrial structure upgrading (Hu et al, 2020;Tang et al, 2021), enterprise competitiveness Sun et al, 2022), technology innovation (Zhu et al, 2019;Li et al, 2022), energy transformation (Yu et al, 2022), and promotion of foreign direct investment (Liu et al, 2020); these scholars confirmed the positive role of the CETS using different indicator systems. However, the problem is that although the aforementioned indicator system can also meet the requirements of policy evaluation, has the overall operation quality of economy has changed after the implementation of CETS?…”
Section: Literaturementioning
confidence: 93%
See 1 more Smart Citation
“…There are many literatures on the evaluation of the CETS's economic effect, mainly focusing on energy saving and emission reduction (Xuan et al, 2020;Tian et al, 2022), industrial structure upgrading (Hu et al, 2020;Tang et al, 2021), enterprise competitiveness Sun et al, 2022), technology innovation (Zhu et al, 2019;Li et al, 2022), energy transformation (Yu et al, 2022), and promotion of foreign direct investment (Liu et al, 2020); these scholars confirmed the positive role of the CETS using different indicator systems. However, the problem is that although the aforementioned indicator system can also meet the requirements of policy evaluation, has the overall operation quality of economy has changed after the implementation of CETS?…”
Section: Literaturementioning
confidence: 93%
“…Stavins (1995), Rogge et al (2011), and other scholars have shown that a properly designed emissions trading system will guide enterprises to continuously improve their production process through market signals, and finally find a new equilibrium point of marginal revenue and marginal cost to promote the equalization of marginal emission reduction costs in the whole market. Therefore, in studies by Montgomery (1972), Karp and Zhang (2005), Bayer and Aklin (2020), Yu et al (2021), , Tian et al (2022), and other studies, CETS is described as a successful case. Using various analytical tools, scholars have measured the effect of the CETS on agricultural productivity (Hua et al, 2022), spatial spillover effect (Wu and Wang, 2022), and pollution reduction performance (Yan et al, 2020).…”
Section: Literaturementioning
confidence: 96%
“…This paper explores the effect of the development level of the DE on urban CE. At present, there are two main choices for explanatory variables in the research on CE reduction: one is per capita CE [ 49 , 50 ] and the other is total emissions [ 51 , 52 ]. This paper selected the total urban emissions as the explained variable in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Chen et al (2022) find that urbanization worsens carbon emissions. Tian et al (2022) report that an emission trading system helps to reduce carbon emissions. This strand of literature suggests that there are several contributing factors that impact carbon emissions.…”
Section: Carbon Riskmentioning
confidence: 99%